2023
DOI: 10.25082/amler.2023.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Greek secondary school teachers' degree of readiness in adopting mobile learning in the educational process

Abstract: Much has been written and researched about mobile learning. The positive impact it has on education has been highlighted in these studies. However, the role of the teacher is also of fundamental importance. Teachers are not sidelined. On the contrary, they take on a different role: reinforcer and guide. Therefore, it is necessary to consider teachers' opinions on mobile learning. It was considered necessary to investigate the degree of readiness of secondary school teachers to adopt Mobile Learning, focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Additionally, OSBL has a stronger influence on ICTSE than PUBL. This difference in influence can be attributed to the fact that self-efficacy depends on organizational training support (Troulinaki, 2023), while the usefulness of support for blended learning is more dependent on individual motivation (Ba¨chtold et al, 2023). Therefore, a causal relationship exists between OSBL and ICTSE, which can also increase students' perceptions of the usefulness of blended learning and significantly and positively predicts SSBL via SEBL.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, OSBL has a stronger influence on ICTSE than PUBL. This difference in influence can be attributed to the fact that self-efficacy depends on organizational training support (Troulinaki, 2023), while the usefulness of support for blended learning is more dependent on individual motivation (Ba¨chtold et al, 2023). Therefore, a causal relationship exists between OSBL and ICTSE, which can also increase students' perceptions of the usefulness of blended learning and significantly and positively predicts SSBL via SEBL.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Esteban-Millat et al (2018) confirmed that PU is the main external motivation that affects attitudes and behaviors toward using IS. Troulinaki (2023) concluded through empirical comparisons that those who have received training related to IS find it more useful and effective than those who have not. In TAM, the only uncertain variable of PU is the antecedent variable, which provides a valuable basis for researchers to develop, extend, and modify the structure of TAM in different contexts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…An essential issue of e-learning while using various video conference platforms is whiteboard functionality. Traditional whiteboards are highly effective visual communication and collaboration tools, allowing instructors to sketch diagrams, solve equations, and brainstorm ideas in real time (Dahal et al, 2022;Troulinaki, 2023). However, many video conferencing platforms offer limited whiteboard features compared to a physical whiteboard.…”
Section: Introductionmentioning
confidence: 99%